Threshold Friction Velocity Influenced by the Crust Cover of Soils in the Columbia Plateau. Issue 1 (1st February 2019) - Pi, Huawei; Sharratt, Brenton
Abstract : Core Ideas: Particulate emissions from agricultural lands threaten air quality. Soil crusts reduce emissions by increasing threshold friction velocity. Threshold friction velocity was determined from temporal variations in particle concentrations inside a wind tunnel. Crust cover increased threshold friction velocity, particularly under 60 and 100% crust cover. Soil crusts provide stability and protection against wind erosion from semiarid and arid lands. Although erosion is initiated when the friction velocity ( U *) exceeds the threshold friction velocity ( U *t ) of soils, there is little information available on the effect of soil crust cover on U *t . The objective of this study was therefore to evaluate the effect of soil crust cover on the U *t of five loessial soils of the Columbia Plateau, United States. Soil samples were sieved and the erodible fraction was placed in 1 by 0.2 by 0.015 m trays. Water drops 4.5 mm in diameter were applied to the soil surface at a known density, which, after drying, created various percentages of crust cover. The trays were placed inside a wind tunnel to assess U *t . which was determined by systematically wind speed until an increase was observed in total suspended particulate concentration inside the tunnel. No significant differences in U *t were found among 0, 15, and 30% cover but significant differences in U *t were found between 60 and 100% cover. The U *t of 100% crust cover was about twice that of 0% cover. Crust crushing energy, which influences abrasion, did not vary across crust cover treatments. The Single‐event Wind Erosion Evaluation Program (SWEEP) revealed the similar influence of crust cover on U *t . The SWEEP adequately simulated U *t for 0, 15, and 30% crust cover but overestimated U *t for 60 and 100% cover. These results suggest that crusts effectively protect the soil from wind erosion by increasing U *t .